SUN-138 Functional Characterization of Tumor-Associated Germline TMEM127 Variants Reveals Novel Insights into Membrane Topology and Protein Trafficking - Flores, Shahida (J Endocr Soc, 2020)
TMEM127, a tumor suppressor gene in hereditary pheochromocytomas and paragangliomas, encodes for a poorly characterized, ubiquitous, transmembrane (TM) protein with no substantial identity to any other protein and no identifiable functional domains other than putative TM domains. The function and regulation of TMEM127 remain poorly defined which limits prediction of pathogenicity of germline TMEM127 variants. Characterizing structure-function features of TMEM127 is relevant for understanding how dysfunction of this tumor suppressor can lead to inherited tumors. Moreover, a better understanding of TMEM127 functional domains and critical residues will increase our ability to identify pathogenic variants which will improve interpretation of genetic screening results and help guide clinical decisions for patients and their families. In this study, we investigated subcellular localization and steady-state levels of patient-derived, tumor-associated, germline TMEM127 variants (n=21; 16 missense and 5 truncating/frameshift/indel variants). We used confocal immunofluorescence and immunoblot analysis of GFP-TMEM127 constructs expressed in HEK293T cells. Wild-type (WT) TMEM127 localized predominantly to endo-lysosomal vesicles (punctate) with some plasma membrane localization. The localization of variant TMEM127 proteins displayed three distinct patterns: punctate (similar to WT), diffuse (cytoplasmic), and plasma membrane only. All diffuse proteins, and a few punctate proteins, decreased at a faster rate than the WT suggesting instability. Variants resulting in diffuse proteins occurred within TM domains and indicated that membrane binding ability was lost. This observation, supported by in silico analysis and selective permeability assays, led us to conclude that TMEM127 is a four-TM protein, not a three-TM protein, as previously predicted, with a novel TM domain in the N-terminus. One variant with predominantly plasma membrane localization indicated that membrane binding ability was maintained but internalization capability was lost. We identified an atypical, extended acidic dileucine motif in the C-terminal which is responsible for TMEM127 internalization and showed that it is mediated by clathrin. Our findings provide novel insights into structure-function features of TMEM127 which will allow for better understanding of its physiological role and improved prediction of pathogenic variants.